2q37 Deletion syndrome confirmed by high-resolution cytogenetic analysis - Eun-Kyung Cho; Jinsup Kim; Aram Yang; Sung Yoon Cho; Dong-Kyu Jin (Korean Society of Pediatric Endocrinology, 2017)
Chromosome 2q37 deletion syndrome is a rare chromosomal disorder characterized by mild to moderate developmental delay, brachydactyly of the third to fifth digits or toes, short stature, obesity, hypotonia, a characteristic facial appearance, and autism spectrum disorder. Here, we report on a patient with 2q37 deletion presenting with dilated cardiomyopathy (DCMP). Congenital heart malformations have been noted in up to 20% of patients with 2q37 deletions. However, DCMP has not been reported in 2q37 deletion patients previously. The patient exhibited the characteristic facial appearance (a flat nasal bridge, deep-set eyes, arched eyebrows, and a thin upper lip), developmental delay, mild mental retardation, peripheral nerve palsy, and Albright hereditary osteodystrophy (AHO)-like phenotypes (short stature and brachydactyly). Conventional chromosomal analysis results were normal; however, microarray-based comparative genomic hybridization revealed terminal deletion at 2q37.1q37.3. In addition, the patient was confirmed to have partial growth hormone (GH) deficiency and had shown a significant increase in growth rate after substitutive GH therapy. Chromosome 2q37 deletion syndrome should be considered in the differential diagnosis of patients presenting with AHO features, especially in the presence of facial dysmorphism. When patients are suspected of having a 2q37 deletion, high-resolution cytogenetic analysis is recommended.